Response of Microclimate Formation, Growth, and Yield of Cucumber (Cucumis sativus L.) to Mulch Application and Planting Spacing Variation under Dryland Conditions - Pasaribu, Angelika; Hariyono, Didik; Fajriani, Sisca (CV. Komunitas Dunia Peternakan, 2026)
Cucumber (Cucumis sativus L.) is a high-value horticultural commodity, but its production has declined due to drought stress affecting plant physiology and female flower formation. To address this issue, the use of mulch and planting spacing can modify the microclimate and reduce inter-plant competition. This study aimed to evaluate the effects of rice straw mulch and planting spacing on the growth, yield, and environmental conditions of cucumber. A factorial randomized block design was employed with two factors: mulch (no mulch and rice straw mulch) and planting spacing (40 × 60 cm, 50 × 50 cm, and 60 × 40 cm), replicated four times. Observed variables included vegetative growth, number of male and female flower, yield, soil temperature, and soil moisture. The study was conducted from June to August 2025 at the Agrotechnopark, Brawijaya University. The results showed a significant interaction between rice straw mulch and 50 × 50 cm planting spacing on fruit diameter, fruit length, fruit weight per fruit, fruit weight per plant, and plant productivity. This combination also created a more stable soil environment. It is concluded that the application of rice straw mulch with a 50 × 50 cm planting spacing is the optimal combination for enhancing cucumber growth and yield through improved microclimate conditions, however, these research are limited to a single growing season and a single experimental location.